Simultaneous upgrading of biomass-derived sugars to HMF/furfural via enzymatically isomerized ketose intermediates - Wei Wang; Ashutosh Mittal; Heidi Pilath; Xiaowen Chen; Melvin P. Tucker; David K. Johnson (Biotechnology for Biofuels, 2019)
Abstract Background Recently, exploring fermentative or chemical pathways that convert biomass-derived sugars to fuels/chemicals has attracted a lot of interest from many researchers. We are investigating a hydrocarbon pathway from mixed sugars via 5-hydroxymethyl furfural (HMF) and furfural intermediates. To achieve this goal, we must first convert glucose and xylose to HMF and furfural in favorable yields. Current processes to produce HMF/furfural generally involve the use of acid catalysts in biphasic systems or solvents such as ionic liquids. However, the yield from transforming glucose to HMF is lower than the yield of furfural from xylose. Results In this study, we present an efficient chemical pathway simultaneously transforming glucose and xylose to HMF and furfural via ketose intermediates, i.e., fructose and xylulose, which were generated from glucose and xylose via enzymatic isomerization. In the enzymatic isomerization, by adding sodium borate to complex with the ketoses, xylose conversion reached equilibrium after 2 h with a conversion of 91% and glucose conversion reached 84% after 4 h. By enzymatically isomerizing the aldoses to ketoses, the following dehydration reactions to HMF and furfural could be performed at low process temperatures (i.e., 110–120 °C) minimizing the side reactions of the sugars and limiting the degradation of furfurals to humins and carboxylic acids. At 120 °C, pH 0.5, and 15 min reaction time, mixed ketose sugars were converted to HMF and furfural in yields of 77% and 96%, respectively (based on starting aldose concentrations). Conclusion Taken together, our results demonstrate that this combined biological and chemical process could be an effective pathway to simultaneously convert biomass-derived glucose and xylose to HMF and furfural, for use as intermediates in the production of hydrocarbons.